2013
DOI: 10.1051/0004-6361/201220701
|View full text |Cite
|
Sign up to set email alerts
|

Asteroids’ physical models from combined dense and sparse photometry and scaling of the YORP effect by the observed obliquity distribution

Abstract: Context. The larger number of models of asteroid shapes and their rotational states derived by the lightcurve inversion give us better insight into both the nature of individual objects and the whole asteroid population. With a larger statistical sample we can study the physical properties of asteroid populations, such as main-belt asteroids or individual asteroid families, in more detail. Shape models can also be used in combination with other types of observational data (IR, adaptive optics images, stellar o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 37 publications
4
44
1
Order By: Relevance
“…9 and 10) yields parameters near d YORP ¼ 0:4; c reorient ¼ 0:9, and c YORP ¼ 0:5-0.7, in agreement with the modeling work in Hanuš et al (2013). This suggests we need YORP to be a little weaker than the nominal values (value of unity), with more time between YORP cycles.…”
Section: Constraining the Static Yorp Monte Carlo Modelsupporting
confidence: 79%
See 2 more Smart Citations
“…9 and 10) yields parameters near d YORP ¼ 0:4; c reorient ¼ 0:9, and c YORP ¼ 0:5-0.7, in agreement with the modeling work in Hanuš et al (2013). This suggests we need YORP to be a little weaker than the nominal values (value of unity), with more time between YORP cycles.…”
Section: Constraining the Static Yorp Monte Carlo Modelsupporting
confidence: 79%
“…As one moves to larger diameters, the obliquities spread somewhat to lower latitudes. Hanuš et al (2011Hanuš et al ( , 2013 concluded that their findings were compatible with a sample of objects that evolved due to the YORP effect.…”
Section: Constraining the Static Yorp Monte Carlo Modelmentioning
confidence: 72%
See 1 more Smart Citation
“…Combining these datasets with dense lightcurves allowed some authors to increase the modelled population of asteroids from 100 (classical photometry) to 400 (combination of classical and sparse photometric data), using a modified version of the convex lightcurve inversion method (e.g. [17], [18]). The resulting models resemble the ones obtained with dense lightcurves (are equivalent in terms of spin solution) but the shape model is usually a low-resolution, "angular" convex shape, due to the limited quality of the data.…”
Section: Shape Modelsmentioning
confidence: 99%
“…Since the publication of the method, models of about 500 asteroids were derived by this technique (Ďurech et al, 2009;Ďurech et al, 2011;Hanuš et al, 2011Hanuš et al, , 2013bMarciniak et al, 2011, for example); most of them are publicly available in the Database of Asteroid Models from Inversion Techniques (DAMIT 1 , Durech et al, 2010). At this site, the source codes for the lightcurve inversion called convexinv can be downloaded.…”
Section: Asteroid Lightcurve Inversionmentioning
confidence: 99%